P-004 Publishing Title: Incidence of Large Vessel Occlusions Amongst All Hospital Discharges for Acute Ischemic Stroke – Estimating a Thrombectomy Eligible Population. (29th July 2016) - Rai, A; Link, P; Boo, S; Domico, J; Lucke-Wold, N; Tarabishy, A; Carpenter, J
Abstract : Background: Endovascular therapy has been endorsed for emergent large vessel occlusions (ELVO). However the incidence of ELVO is ill defined and speculative. A methodical estimate of these patients is important for developing systems of care, resource allocation and market projections. Objective: To determine the national burden of ELVO by extrapolating these rates from a tertiary rural health system that captures over 85% of all ischemic strokes within its large rural catchment area to the national inpatient sample (NIS) database. Methodology: All hospital discharges with a primary or secondary diagnosis of AIS (ICD-9 433.xx, 434.xx, 435.xx) over a 3 year period in a rural tertiary health system in the "stroke-belt" were evaluated for ELVO (ICA-T, MCA, BA) based on admission CT or MR angiography. For anterior circulation strokes, an ASPECTS ≥6 was considered favorable for thrombectomy. The same ICD-9 codes were utilized to query the NIS-database to determine all AIS hospital discharges nationally and the ELVO rates were estimated based on the results from our catchment population. Results: There were 2757 AIS hospital discharges over a 3 year period (March 2012 to March 2015) based on the selected ICD-9 codes. An ELVO was present in 324 (11.8%) of these patients. Out of these, M1-occlusion was present in 232 (71.6%), ICA-T in 37 (11.4%) and BA in 55 (17%) patients. The majority of ELVO patients (n = 174, 53.7%) presented within 6 hours of last seen normal (LSN). Of the remaining 150 (46.3%) patients: 45 (13.6%) presented at 6–12 hours, 60 (18.5%) at 12–24 hours and 27 (8.3%) at greater than 24 hours of LSN. There were 19 (5.9%) patients with unknown LSN. For anterior circulation (n = 269, 83%) an ASPECTS ≥6 was observed in 118 of 150 (78.7%) patient presenting within 6 hours of LSN and in 66 of 1119 (55.5%) patients presenting after 6 hours of LSN (p < 0.0001). The same ICD-9 codes for the NIS-database returned 1, 135, 030 AIS discharges nationally for 2013. Applying the statistics from our population to the NIS-database yields 133, 388 large vessel strokes nationally (95, 512 M1, 15, 233 ICA-T and 22, 643 BA). Of these, 71, 634 patients are estimated to present within 6 hours and 61, 754 after 6 hours of LSN. There could be 48, 579 patients within 6 hours and 27, 172 patients after 6 hours with an ASPECTS ≥6 resulting in a total of 75, 751 potential thrombectomy eligible patients in the anterior circulation. Conclusion: Almost 12% of the patients in our large rural sample of AIS hospital discharges presented with an ELVO. This translated to 133, 388 patients when extrapolated to the NIS-database for 2013. An estimated 48, 579 patients within 6 hours and 27, 172 patients after 6 hours could be thrombectomy eligible based on ASPECTS ≥6. An additional 22, 643 patients were estimated to have a basilar occlusion. These are estimates based on a stroke center within a healthcare system serving a large rural population and probably represent the upper limit since the area under study has one of the highest ischemic stroke rates in the country. These numbers can also be subject to regional variations but nonetheless serve as a starting point for estimating the ELVO stroke burden and for planning systems of care. Disclosures: A. Rai: 1; C; Stryker Neurovascular. 2; C; Stryker Neurovascular. P. Link: None. S. Boo: None. J. Domico: None. N. Lucke-Wold: None. A. Tarabishy: None. J. Carpenter: None.